Tantangan dan Peluang Pengimplementasian Kurikulum Merdeka di SD/MI Sumatera Selatan - Astuti, Mardiah; Ismail, Fajri; Herlina, Herlina; Ayuni, Anindia Qurrota; Nurazizah, Nurazizah; Tahira, Rima; Salsabila, Yuni; Salika, Jingga (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the implementation process of the Merdeka Curriculum in MI/SD in South Sumatra. Several issues arise during the implementation process, including teacher readiness, limited training, inadequate infrastructure, and community understanding. This research is a qualitative study with a field approach, employing data collection techniques such as interviews, observations, and documentation. The informants in this study consist of 25 individuals, including educators, school principals, and students. The process of data processing and analysis is conducted in three stages: data reduction, data presentation, and conclusion drawing. Data validity is ensured through triangulation methods, which include source, technique, and time triangulation. Based on the results and discussion, the curriculum provides opportunities to enhance learning through a flexible, student-centered approach and the development of character and 21st-century skills. Several schools in South Sumatra have implemented project-based learning, differentiated instruction, and technology to create active and innovative learning environments. Despite the challenges, the Merdeka Curriculum has a positive impact on improving the quality of education and preparing a creative and independent younger generation